Method for judging whether petroleum coke is doped in lignite

By performing two high-temperature ashing treatments on the lignite samples and measuring the sulfur content, the problem of difficulty in determining whether lignite is doped with petroleum coke in the prior art is solved, and fast and accurate detection results are achieved, ensuring the rationality of coal-fired ratio in thermal power plants.

CN119901897APending Publication Date: 2025-04-29BAISE MINING GRP CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510092803.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately determine whether lignite is doped with petroleum coke, which leads to the problem of unreasonable coal-fired ratios in thermal power plants during combustion.

Method used

By performing two high-temperature ashing treatments on the lignite sample to be tested, the sulfur content W1 of the primary residue and the sulfur content W2 of the secondary residue are measured, and compared with the sulfur content W0 of the original sample to determine whether petroleum coke is doped.

Benefits of technology

It realizes a rapid and accurate judgment of whether lignite is doped with petroleum coke, avoiding the problem of unreasonable coal allocation ratio in thermal power plants during combustion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119901897A_ABST
    Figure CN119901897A_ABST
Patent Text Reader

Abstract

The invention provides a method for judging whether lignite is doped with petroleum coke, and relates to the technical field of coal detection.The method includes the steps that according to the ashing rate of lignite and petroleum coke at the high temperature and the difference of the sulfur content in residues obtained after ashing treatment, high-temperature ashing treatment is conducted on a lignite sample to be detected twice, and the content of sulfur in the residues is determined; measuring the sulfur content W1 of the primary residue and the sulfur content W2 of the secondary residue, and then comparing the W1, the W2 and the sulfur content W0 of the to-be-detected lignite sample, so as to judge whether the to-be-detected lignite sample is doped with the petroleum coke or not. By adopting the method disclosed by the invention, whether the petroleum coke is doped in the lignite or not can be quickly and accurately judged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal detection, and in particular to a method for judging whether lignite is mixed with petroleum coke. Background Art

[0002] As one of the main raw materials of thermal power plants, lignite needs to be inspected and accepted for quality when it is purchased into the factory. In order to improve the calorific value of lignite products, some suppliers of lignite products deliberately add a certain amount of petroleum coke into pure lignite, which will have an adverse effect on the normal use of lignite in the later stage. For example: During the combustion process of the boiler of a thermal power plant, in order to ensure the efficient and economic operation of the boiler, the thermal power plant will reasonably blend the coal and then burn it. If the lignite entering the factory is mixed with petroleum coke, it will affect the rationality of the calculation of the coal blending ratio. For this reason, before the lignite is put into use, it is necessary to confirm that there is no petroleum coke mixed in the lignite. At present, the coal entering the factory is mainly inspected and accepted through appearance inspection and sample testing. However, since the appearance of lignite powder and petroleum coke powder is similar, it is often impossible to effectively distinguish whether the lignite is mixed with petroleum coke through appearance inspection. Therefore, how to quickly and accurately determine whether the lignite product is mixed with petroleum coke has become a technical problem that needs to be solved urgently. Summary of the invention

[0003] The problem solved by the invention is: how to quickly and accurately judge whether the lignite product is mixed with petroleum coke.

[0004] In order to solve the above problems, the present invention provides a method for determining whether lignite is doped with petroleum coke, comprising:

[0005] Obtain the sulfur content of the sample to be tested, recorded as W0;

[0006] The sample to be tested is subjected to a first ashing treatment to obtain a primary residue, and the sulfur content of the primary residue is measured and recorded as W1;

[0007] The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is measured and recorded as W2;

[0008] Whether the sample to be tested is doped with petroleum coke is determined based on W0, W1, and W2.

[0009] Optionally, judging whether the sample to be tested is doped with petroleum coke according to W0, W1, and W2 includes:

[0010] If W1 and W2 are both less than or equal to W0, it is judged that the sample to be tested is not mixed with petroleum coke and is a pure lignite product;

[0011] If W1 and W2 are both greater than W0, and the absolute value A of the difference between W1 and W2 is less than %0.1, it is determined that petroleum coke is doped in the sample to be tested.

[0012] Optionally, the temperature of the first ashing treatment and the second ashing treatment are both above 250°C.

[0013] Optionally, the temperature of the first ashing treatment and the second ashing treatment are both 840°C to 860°C.

[0014] Optionally, the first ashing treatment lasts for 7 to 9 minutes, and the second ashing treatment lasts for 4 to 6 minutes.

[0015] Optionally, the particle size of the sample to be tested is below 0.2 mm.

[0016] Optionally, the sample to be tested is a sample that has been dried.

[0017] Optionally, the sample to be tested is an air-dried coal sample.

[0018] Optionally, the first ashing process and the second ashing process are performed in a muffle furnace. Optionally, during the first ashing process and the second ashing process, a gap of 0.9 cm to 1.1 cm is left on the door of the muffle furnace.

[0019] Compared with the related art, the present invention is based on the difference in the ash rate of lignite and petroleum coke at high temperature and the sulfur content in the residue obtained after the ash treatment, by performing two high-temperature ash treatments on the lignite sample to be tested, measuring the sulfur content W1 of the first residue and the sulfur content W2 of the second residue, and then comparing W1, W2 and the sulfur content W0 of the lignite sample to be tested, so as to determine whether the lignite sample to be tested is doped with petroleum coke. The method of the present invention can quickly and accurately determine whether lignite is doped with petroleum coke. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The figure is a flow chart of a method for determining whether lignite is doped with petroleum coke in an embodiment of the present invention. DETAILED DESCRIPTION

[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.

[0022] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0023] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, the meaning of "multiple" is two or more.

[0024] It should be noted that the method of the present invention can be applied to at least the following situations: For example, during the process of testing lignite products entering the factory, the applicant found that the lignite products provided by certain specific lignite manufacturers mainly have the following two situations: 1. The lignite products are mixed with petroleum coke and are non-pure lignite products. 2. The lignite products are not mixed with petroleum coke and are pure lignite products. Therefore, the method of the present invention can be used to determine whether the lignite products of these specific manufacturers are mixed with petroleum coke.

[0025] It should be noted that the pure lignite product in the present invention refers to a conventional undoped lignite product.

[0026] Before lignite is put into use, it is necessary to confirm whether it is mixed with petroleum coke. At present, the main way to inspect lignite before it enters the factory is to identify it through appearance inspection. However, since the appearance of lignite powder and petroleum coke powder is similar, it is often impossible to effectively distinguish whether lignite is mixed with petroleum coke through appearance inspection. Studies have found that compared with lignite, petroleum coke has a slower ashing speed at high temperature, and the sulfur content in the residue obtained after ashing treatment is higher.

[0027] Based on the above considerations, if Figure 1 As shown, an embodiment of the present invention provides a method for determining whether lignite is doped with petroleum coke, comprising:

[0028] Obtain the sulfur content of the sample to be tested, recorded as W0;

[0029] The sample to be tested is subjected to a first ashing treatment to obtain a primary residue, and the sulfur content of the primary residue is measured and recorded as W1;

[0030] The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is measured and recorded as W2;

[0031] Whether the sample to be tested is doped with petroleum coke is determined based on W0, W1, and W2.

[0032] It is understandable that petroleum coke is an important petrochemical product, which is obtained by calcining petroleum residue at high temperature. Petroleum coke mainly includes carbon and impurities, including sulfur, etc. Generally speaking, the calcination temperature of petroleum coke is between 1300°C and 1500°C. At this temperature, the impurities in the petroleum coke can be fully released, including the sulfur components therein; and the ash temperature of lignite is about 850°C, which can release the sulfur impurities contained in it. Therefore, according to the difference in the ash rate of lignite and petroleum coke at high temperature and the sulfur content in the residue obtained after ash treatment, the embodiment of the present invention performs two high-temperature ash treatments on the lignite sample to be tested, measures the sulfur content W1 of the first residue and the sulfur content W2 of the second residue, and then compares W1, W2, and the sulfur content W0 of the lignite sample to be tested, so as to determine whether the lignite sample to be tested is doped with petroleum coke. The method of the present invention can quickly and accurately determine whether lignite is doped with petroleum coke.

[0033] In some embodiments of the present invention, specifically, judging whether the sample to be tested is doped with petroleum coke according to W0, W1, and W2 includes:

[0034] If W1 and W2 are both less than or equal to W0, it is judged that the sample to be tested is not mixed with petroleum coke and is a pure lignite product;

[0035] If W1 and W2 are both greater than W0, and the absolute value A of the difference between W1 and W2 is less than 0.1%, it is determined that petroleum coke is doped in the sample to be tested.

[0036] In this embodiment, W1, W2, and the sulfur content W0 of the lignite sample to be tested are compared. If W1 and W2 are both less than or equal to W0, it can be determined that the sample to be tested is not doped with petroleum coke and is a pure lignite product; if W1 and W2 are both greater than W0, and the absolute value A of the difference between W1 and W2 is less than 0.1%, it is determined that the sample to be tested is doped with petroleum coke; in addition, when the lignite sample to be tested is doped with sawdust, the absolute value A of the difference between W1 and W2 is greater than 0.2%. Therefore, when W1 and W2 are both greater than W0, A is further analyzed to exclude the possibility of sawdust being doped in the lignite sample to be tested, thereby making the judgment accuracy of the method of the present invention higher.

[0037] In some embodiments of the present invention, the temperature of the first ashing treatment and the second ashing treatment are both above 250°C; preferably, the temperature of the first ashing treatment and the second ashing treatment are both 840°C to 860°C. It has been found through experiments that the ashing degree of petroleum coke and lignite has a certain relationship with the ashing temperature and ashing time. For example, the ashing degree of the sample can reach 50% to 80% after about 16 hours of ashing treatment at 250°C to 350°C. When the temperature of the first ashing treatment and the second ashing treatment is 840°C to 860°C, the ashing speed of the sample to be tested is faster and the detection efficiency is higher.

[0038] In some embodiments of the present invention, the first ashing treatment lasts for 7 to 9 minutes, and the second ashing treatment lasts for 4 to 6 minutes.

[0039] In some embodiments of the present invention, preferably, the particle size of the sample to be tested is less than 0.2 mm. The particle size of the sample to be tested is controlled to be less than 0.2 mm to ensure that the sample to be tested can be more fully exposed to oxygen, thereby being more completely ashed.

[0040] In some embodiments of the present invention, the sample to be tested is a sample that has been dried. Preferably, the sample to be tested is an air-dried coal sample.

[0041] In some embodiments of the present invention, the first ashing process and the second ashing process are performed in a muffle furnace, and during the first ashing process and the second ashing process, a gap of 0.9 cm to 1.1 cm is left on the door of the muffle furnace. In this embodiment, a gap of 0.9 cm to 1.1 cm is left on the door of the muffle furnace to ensure that the sample to be tested is fully ashed, but the gap should not be too large, otherwise deflagration will occur.

[0042] In some embodiments of the present invention, the sulfur content of the measured residue is measured by a sulfur meter.

[0043] The present invention is further described below in conjunction with specific examples. It should be noted that the lignite samples to be tested used in the following examples are lignite products provided by various manufacturers.

[0044] Example 1

[0045] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested. The sulfur content W0 of the lignite sample to be tested is 1.76%.

[0046] A2. Performing a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detecting the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 1.39%.

[0047] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 1.02%.

[0048] Since the test results of Example 1 show that W1 and W2 are both less than W0, it is a case where there is no doping with petroleum coke. It is determined that the lignite sample to be tested in Example 1 is not doped with petroleum coke and is a pure lignite product.

[0049] At the same time, in view of the above test conclusions, it was confirmed with the manufacturer that the lignite sample to be tested in Example 1 was not mixed with petroleum coke and was a pure lignite product. The test results of Example 1 were accurate.

[0050] Example 2

[0051] The difference from Example 1 is that in step A1, the temperature of the first ashing treatment is 840°C, the time is 9 minutes, and W1 is 1.36%; in step A2, the temperature of the second ashing treatment is 840°C, the time is 4 minutes, and W2 is 1.01%.

[0052] Since the test results of Example 2 show that W1 and W2 are both less than W0, it is a case where there is no doping with petroleum coke. It is determined that the lignite sample to be tested in Example 2 is not doped with petroleum coke and is a pure lignite product.

[0053] At the same time, in view of the above test conclusions, after confirmation with the manufacturer, the lignite sample to be tested in Example 2 is not mixed with petroleum coke and is a pure lignite product. The test results of Example 2 are accurate.

[0054] Example 3

[0055] The difference from Example 1 is that in step A1, the temperature of the first ashing treatment is 860°C, the time is 7 minutes, and W1 is 1.34%; in step A2, the temperature of the second ashing treatment is 860°C, the time is 6 minutes, and W2 is 1.04%.

[0056] Since the test results of Example 3 show that W1 and W2 are both less than W0, it is a case where there is no doping with petroleum coke. It is determined that the lignite sample to be tested in Example 3 is not doped with petroleum coke and is a pure lignite product.

[0057] At the same time, in view of the above test conclusions, it was confirmed with the manufacturer that the lignite sample to be tested in Example 3 was not mixed with petroleum coke and was a pure lignite product. The test results of Example 3 were accurate.

[0058] Example 4

[0059] The difference from Example 1 is that in step A1, the temperature of the first ashing treatment is 250°C, the time is 12h, and W1 is 1.40%; in step A2, the temperature of the second ashing treatment is 250°C, the time is 4h, and W2 is 1.10%.

[0060] Since the test results of Example 4 show that W1 and W2 are both less than W0, it is a case where there is no doping with petroleum coke. It is determined that the lignite sample to be tested in Example 4 is not doped with petroleum coke and is a pure lignite product.

[0061] At the same time, in view of the above test conclusions, it was confirmed with the manufacturer that the lignite sample to be tested in Example 4 was not mixed with petroleum coke and was a pure lignite product. The test results of Example 4 were accurate.

[0062] Example 5

[0063] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested, and find that the sulfur content W0 of the lignite sample to be tested is 1.25%.

[0064] A2. Performing a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detecting the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 0.63%.

[0065] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 0.51%.

[0066] Since the test results of Example 5 show that W1 and W2 are both less than W0, it is a case where there is no doping with petroleum coke. It is determined that the lignite sample to be tested in Example 5 is not doped with petroleum coke and is a pure lignite product.

[0067] At the same time, in view of the above test conclusions, it was confirmed with the manufacturer that the lignite sample to be tested in Example 5 was not mixed with petroleum coke and was a pure lignite product. The test results of Example 5 were accurate.

[0068] Example 6

[0069] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested. The sulfur content W0 of the lignite sample to be tested is 1.66%.

[0070] A2. Performing a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detecting the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 0.97%.

[0071] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 0.42%.

[0072] Since the test results of Example 6 show that W1 and W2 are both less than W0, it is a case where there is no doping with petroleum coke. It is determined that the lignite sample to be tested in Example 6 is not doped with petroleum coke and is a pure lignite product.

[0073] At the same time, in view of the above test conclusions, it was confirmed with the manufacturer that the lignite sample to be tested in Example 6 was not mixed with petroleum coke and was a pure lignite product. The test results of Example 6 were accurate.

[0074] Example 7

[0075] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested. The sulfur content W0 of the lignite sample to be tested is 1.47%.

[0076] A2. Performing a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detecting the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 2.15%.

[0077] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 2.08%.

[0078] Since the test results of Example 7 show that W1 and W2 are both greater than W0, and the absolute value of the difference between W1 and W2 A=|W1-W2|=0.07%, which is less than 0.1%, it is a case of doped petroleum coke. It is determined that the lignite sample to be tested in Example 7 is doped with petroleum coke.

[0079] At the same time, in view of the above test conclusions, after confirmation with the manufacturer, the lignite sample to be tested in Example 7 is doped with petroleum coke, and the test results of Example 7 are accurate.

[0080] Example 8

[0081] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested. The sulfur content W0 of the lignite sample to be tested is 1.41%.

[0082] A2. Performing a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detecting the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 2.67%.

[0083] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 2.63%.

[0084] Since the test results of Example 8 show that W1 and W2 are both greater than W0, and the absolute value of the difference between W1 and W2 A=|W1-W2|=0.04%, which is less than 0.1%, it is a case of doped petroleum coke. It is determined that the lignite sample to be tested in Example 8 is doped with petroleum coke.

[0085] At the same time, in view of the above test conclusions, it was confirmed with the manufacturer that the lignite sample to be tested in Example 8 was doped with petroleum coke, and the test results of Example 8 were accurate.

[0086] Example 9

[0087] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested. The sulfur content W0 of the lignite sample to be tested is 1.42%.

[0088] A2. Performing a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detecting the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 2.76%.

[0089] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 2.72%.

[0090] Since the test results of Example 9 show that W1 and W2 are both greater than W0, and the absolute value of the difference between W1 and W2 A=|W1-W2|=0.04%, which is less than 0.1%, it is a case of doped petroleum coke. It is determined that the lignite sample to be tested in Example 9 is doped with petroleum coke.

[0091] At the same time, in view of the above test conclusion, it was confirmed with the manufacturer that the lignite sample to be tested in Example 9 was doped with petroleum coke.

[0092] Comparative Example 1

[0093] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested. The sulfur content W0 of the lignite sample to be tested is 1.28%.

[0094] A2. Perform a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detect the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 5.20%.

[0095] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 4.97%.

[0096] Since the test results of Comparative Example 1 show that both W1 and W2 are greater than W0, the possibility that the lignite sample to be tested is a pure lignite product can be preliminarily ruled out. Since the absolute value of the difference between W1 and W2 A = |W1-W2| = 0.23%, which is greater than 0.2%, this is inconsistent with the situation that the lignite sample to be tested is mixed with petroleum coke. Therefore, it is judged that the lignite sample to be tested in Comparative Example 1 is not mixed with petroleum coke.

[0097] At the same time, in view of the above test conclusions, it was confirmed with the manufacturer that the lignite sample to be tested in Comparative Example 1 was not mixed with petroleum coke, but was mixed with sawdust.

[0098] Comparative Example 2

[0099] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested. The sulfur content W0 of the lignite sample to be tested is 1.38%.

[0100] A2. Performing a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detecting the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 5.25%.

[0101] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 4.96%.

[0102] Since the test results of Comparative Example 2 show that both W1 and W2 are greater than W0, the possibility that the lignite sample to be tested is a pure lignite product can be preliminarily ruled out. Since the absolute value of the difference between W1 and W2 A = |W1-W2| = 0.29%, which is greater than 0.2%, this is inconsistent with the situation that the lignite sample to be tested is mixed with petroleum coke. Therefore, it is judged that the lignite sample to be tested in Comparative Example 2 is not mixed with petroleum coke.

[0103] At the same time, in view of the above test conclusions, after confirmation with the manufacturer, the lignite sample to be tested in Comparative Example 2 was not mixed with petroleum coke, but was mixed with sawdust.

[0104] Comparative Example 3

[0105] A1. Take 1 g of the lignite sample to be tested, and test the sulfur content of the lignite sample to be tested, and find that the sulfur content W0 of the lignite sample to be tested is 1.25%.

[0106] A2. Performing a first ashing treatment on the lignite sample to be tested to obtain a primary residue, and detecting the sulfur content of the primary residue to obtain the sulfur content W1 of the primary residue; wherein the temperature of the first ashing treatment is 850° C., the time is 8 min, and W1 is 4.88%.

[0107] A3. The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is detected to obtain the sulfur content W2 of the secondary residue; wherein the temperature of the second ashing treatment is 850° C., the time is 5 min, and W2 is 4.52%.

[0108] Since the test results of Comparative Example 3 show that both W1 and W2 are greater than W0, the possibility that the lignite sample to be tested is a pure lignite product can be preliminarily ruled out. Since the absolute value of the difference between W1 and W2 A = |W1-W2| = 0.36%, which is greater than 0.2%, this is inconsistent with the situation that the lignite sample to be tested is mixed with petroleum coke. Therefore, it is judged that the lignite sample to be tested in Comparative Example 3 is not mixed with petroleum coke.

[0109] At the same time, in view of the above test conclusions, after confirmation with the manufacturer, the lignite sample to be tested in Comparative Example 3 was not mixed with petroleum coke, but was mixed with sawdust.

[0110] Data analysis

[0111] The data detected in Examples 1 to 9 and Comparative Examples 1 to 3 are summarized to obtain Table 1. It can be seen from Table 1 that the lignite samples to be tested in Examples 1 to 6 are not doped with petroleum coke and are pure lignite products. At this time, W1 and W2 are both less than W0. The lignite samples to be tested in Examples 7 to 9 are doped with petroleum coke. At this time, W1 and W2 are both greater than W0, and the absolute value A of the difference between W1 and W2 is less than 0.1%. The lignite samples to be tested in Comparative Examples 1 to 3 are doped with sawdust. At this time, W1 and W2 are both greater than W0, and the absolute value A of the difference between W1 and W2 is large, and A is greater than 0.2%. It can be seen that when the method of the present invention is used to detect the lignite samples to be tested, it can be determined whether the lignite samples to be tested are doped with petroleum coke. In addition, the total time required for the first ashing treatment and the second ashing treatment in Example 4 is longer (about 16 hours), while the total time required for the first ashing treatment and the second ashing treatment in Examples 1 to 3 and Examples 5 to 6 is shorter (about 13 minutes), and the detection efficiency is higher. It can be seen that for the method of the present invention, the detection efficiency of ashing treatment at 840°C to 860°C is higher.

[0112] Table 1

[0113]

[0114] It should be noted that the " / " means the corresponding data is not listed, but it does not affect the data analysis of this application.

[0115] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for determining whether lignite is doped with petroleum coke, characterized in that: include: Obtain the sulfur content of the sample to be tested, recorded as W0; The sample to be tested is subjected to a first ashing treatment to obtain a primary residue, and the sulfur content of the primary residue is measured and recorded as W1; The primary residue is subjected to a second ashing treatment to obtain a secondary residue, and the sulfur content of the secondary residue is measured and recorded as W2; Whether the sample to be tested is doped with petroleum coke is determined based on W0, W1, and W2.

2. The method for determining whether lignite is doped with petroleum coke according to claim 1, characterized in that: The method of judging whether the sample to be tested is doped with petroleum coke according to W0, W1 and W2 includes: If W1 and W2 are both less than or equal to W0, it is judged that the sample to be tested is not mixed with petroleum coke and is a pure lignite product; If W1 and W2 are both greater than W0, and the absolute value A of the difference between W1 and W2 is less than 0.1%, it is determined that petroleum coke is doped in the sample to be tested.

3. The method for determining whether lignite is doped with petroleum coke according to claim 1, characterized in that: The temperatures of the first ashing treatment and the second ashing treatment are both above 250°C.

4. The method for determining whether lignite is doped with petroleum coke according to claim 3, characterized in that: The temperatures of the first ashing treatment and the second ashing treatment are both 840°C to 860°C.

5. The method for determining whether lignite is doped with petroleum coke according to claim 4, characterized in that: The time for the first ashing treatment is 7 minutes to 9 minutes, and the time for the second ashing treatment is 4 minutes to 6 minutes.

6. The method for determining whether lignite is doped with petroleum coke according to claim 1, characterized in that: The particle size of the sample to be tested is below 0.2 mm.

7. The method for determining whether lignite is doped with petroleum coke according to claim 1, characterized in that: The sample to be tested is a sample that has been dried.

8. The method for determining whether lignite is doped with petroleum coke according to claim 7, characterized in that: The sample to be tested is an air-dried coal sample.

9. The method for determining whether lignite is doped with petroleum coke according to claim 1, characterized in that: The first ashing process and the second ashing process are performed in a muffle furnace.

10. The method for determining whether lignite is doped with petroleum coke according to claim 9, characterized in that: During the first ashing treatment and the second ashing treatment, a gap of 0.9 cm to 1.1 cm is left on the door of the muffle furnace.

Citation Information

Patent Citations

  • Near-infrared spectral recognition method for coal adulteration

    CN104390928A

  • Qualitative method for identifying coal tar contained in crude oil

    CN116068091A

  • Methodology for detection of kerosene adulteration in gasoline, motor spirit, aviation turbine fuel and diesel with intrinsic marker

    WO2014087359A1